Enhancing purchase intentions for educational toys: A hybrid model analysis of children’s 3D jigsaw puzzles - Suwen Luo; Pengrui Yang (Acta Psychologica)
The burgeoning children’s toy market underscores the critical role of innovative design in fostering cognitive development and providing entertainment. This study seeks to clarify the overriding factors influencing purchase intentions for three-dimensional jigsaw puzzles designed for children, utilizing an extended Technology Acceptance Model (TAM). Employing a novel toy product that integrates landmarks and traditional Chinese calendars as a case study, this research examines the impact of various design elements on consumer decision-making. A cross-sectional survey was conducted among parents, focusing the analysis on the effects of compatibility, exploratory curiosity, task concentration, perceived ease of use, and social influence on purchase inclinations. The findings reveal that compatibility with users’ pre-existing knowledge and experiences markedly enhances both perceived usefulness and perceived enjoyment. Moreover, aesthetics and perceived ease of use are pivotal in shaping user attitudes and behavioral intentions. This study extends the application of the Technology Acceptance Model framework to encompass non-digital children’s products, offering actionable insights for designers and marketers to enhance the appeal and commercial viability of educational toys.